The Study of Relationship between Changes in the Leading Indicators and the Accounting Profit of the Firms accepted at the Tehran Stock Exchange - M. A. Aghaee; S. Ali Hoseini (مطالعات تجربی حسابداری مالی, 2003)
This study examines the predictability of accounting profit of the firms accepted at the Tehran Stock Exchange by adjusted Random Walk with past changes of Economic Leading Indicators. In random walk model, actual profit numbers of past years are independent variables. This model is based on assumption that behavior of accounting profit is a random Process. Since the economic lead indicators produce accurate signals about future changes of target variables (e.g. accounting profit and stock price of firms), adjustment of actual profit by proportion of change of this indicators in profit forecasting models like random walk model, can produce better forecasting. The result suggests that adjusted random walk model by proportion of change of two lead indicators, broad money supply  and  aggregate loans paid to governmental  and  non-governmental  sectors  by  banking  system of Iran including the three-year  lag, can produce better  forecasting.